Estudo do comportamento mecânico de areias artificialmente cimentadas - Lopes, Francisco Mateus Gomes (2012)
Soil improved with the addition of cement have been utilized as an alternative to the construction of various types of geotechnical works, almost always present economic and environmental advantages. This paper presents a study on the usage of cement in the improvement of mechanical properties of sandy soils, characteristic of the region of Natal, collected from its dunes. This research was made in order to analyze the influence of cement content, voids, and also including water immersion and confining pressure. Samples molded from cement-soil mixtures were tested for unconfined compression tests and triaxial tests. The samples had the percentage of cement mixed in 2.5%, 5% and 10% by weight. The cement agent used was the Portland Cement of High Early strength(CPV-ARI), which promoted agility to the experimental procedure for presenting a rapid gain in strenght. The void ratio used ranged from 0.7 (more compact), 0,9 and 1,1(softer). The soil under study can be considered as pure sand. In general, it can be stated that the larger the amount of cement added to the sand studied is, the greater ultimate strength will be. Likewise, as more compact the soil is, the less void ratio and more resistant it will be present. The confining pressure tends to increase the resistance of the specimens. The cementing adopted grades showed that the use of different criteria for failure did not significantly alter the stress-strain parameters for the sand studied. The angle of friction values were found within the typical range of medium and compact sands. Cementing acted in the sand providing an intercepted cohesion which increased enhancing the potential cementation. In triaxial compression tests, the sand with void ratio is equal to 0.7 and showed the expected behavior for a compact sand while the stress-strain behavior of the same sand with the void ratio of 0.9 tended to be expected for the soft sand as well